The identity of Dicliptera cyclostegia (Acanthaceae) - Yi, Tong; Deng, Yunfei (Phytotaxa, 2019)
Critical examination of herbarium specimens and observations on living plants reveal that the syntypes of Dicliptera cyclostegia belong to Justicia sect. Harnieria and the three gatherings represent a different species each. A lectotype is designated here for the name Dicliptera cyclostegia and a new combination, Justicia cyclostegia is proposed. A detailed description, illustration and distribution map are also provided.